Complete Chromatin Decondensation of Pig Sperm Is Required to Analyze Sperm DNA Breaks With the Comet Assay - Ribas-Maynou, Jordi; Delgado-Bermúdez, Ariadna; Garcia-Bonavila, Estela; Pinart, Elisabeth; Yeste, Marc; Bonet, Sergi (Frontiers in Cell and Developmental Biology, 2021)
Sperm quality is usually evaluated prior to artificial insemination in farm animals. In addition to conventional semen analysis, other biomarkers, such as mitochondrial activity, integrity and lipid disorder of plasma membrane, generation of reactive oxygen species and sperm DNA integrity, have been found to be related to fertility rates in different species. While mounting evidence indicates that the Comet assay is a sensitive method for the detection of DNA breaks, complete sperm chromatin decondensation is required in order to properly analyze the presence of single- and double-strand DNA breaks. In this sense, a previous study showed that longer lysis treatment with proteinase K is needed to achieve complete chromatin decondensation. The current work sought to determine which specific lysis treatment leads to complete chromatin decondensation in pig sperm, as this is needed for the measurement of DNA damage in this species. With this purpose, incubation with a lysis solution containing proteinase K for 0 min, 30 min and 180 min was added to the conventional protocol. The impact of the DNA damage induced by hydrogen peroxide (H2O2; 0.01% and 0.1%) and DNAse I (1U and 4U) was also evaluated. Complete chromatin decondensation was only achieved when a long additional lysis treatment (180 min) was included. Furthermore, Olive Tail Moment and percentage of Tail DNA indicated that a higher amount of DNA breaks was detected when hydrogen peroxide and DNAse I treatments were applied (P<0.05). The comparison of treated and control sperm allowed defining the thresholds for Olive Tail Moment; these thresholds revealed that the percentage of sperm with fragmented DNA determined by the alkaline Comet does not depend on chromatin decondensation (P>0.05). In conclusion, complete chromatin decondensation prior to alkaline and neutral Comet assays is needed to analyze DNA breaks in pig sperm.